Algorithm of the automated control of displacement of the load overall center of gravity of railroad car for railway transportation - Tat’yana A. Vinokurova; Andrey B. Galushkin; Anatoliy A. Rakhmilevich (Вестник Научно-исследовательского института железнодорожного транспорта)
The algorithm is proposed for the automated control of displacement of the load overall center of gravity relative to transversal and/or longitudinal planes of symmetry of the car during railway transportation and decision-making about availability of commercial damages upon results of the car wheel weighting under way by the weighting equipment in cluded in the set of equipment of the systems of the automated commercial visual inspection of trains and cars. The baseline data for calculations includes results of the car wheel weighting and relative error of measurement of the loads with scale set during certification, and the car container weight accepted according to the data of the car in the Automated database of the freight car fleet of JSC “RZD”. Algorithm of the automated control of each type of displacement includes calculation of the actual displacement of the overall load center of gravity in the car, minimax assessment of the calculated value with regard to the error of determination of the parameters values used for calculation, and the conditions of decision-making about availability of commercial fault. Algorithm of static modeling of the bogie wheels loads on the rail is presented, in which the probabilities of excess of the regulatory maximum allowable value by the actual displacement are determined by the Monte Carlo method (loads of eight wheels are randomly broken out with assumption that distribution of their values is normal). Results of static modeling along with the analysis of the data from transportation documents and video image of the car with the freight allow the operator of the train and car visual commercial inspection station to make decision about necessity of the car field inspection for establishing the fact of commercial fault. Examples of calculation according to the proposed algorithm are provided for the case of control of displacement of the load overall center of gravity relative to the transversal plane of the car symmetry, including comparison with calculations without taking into account the errors. Proposed algorithm can be used in the automated train and car commercial inspection system under way during railway transportation as the element of the digital intelligent technology of commercial inspection being developed in the JSC “RZD”.